Sexual Dysfunction in Men With Inflammatory Bowel Disease: A New IBD-Specific Scale. Issue 2 (18th January 2018) - O'Toole, Aoibhlinn; de Silva, Punyanganie S; Marc, Linda G; Ulysse, Christine A; Testa, Marcia A; Ting, Amanda; Moss, Alan; Korzenik, Josh; Friedman, Sonia
Abstract: Background: Men with inflammatory bowel disease (IBD) may have increased sexual dysfunction. To measure the prevalence of sexual dysfunction in our male patients, we aimed to develop a new IBD-specific Male Sexual Dysfunction Scale (the IBD-MSDS). Methods: We used a cross-sectional survey and enrolled male patients (N = 175) ≥18 years old who attended IBD clinics at 2 Boston hospitals. We collected information on sexual functioning via a 15-item scale. General male sexual functioning was measured using the International Index of Erectile Dysfunction (IIEF); the Patient Health Questionnaire (PHQ-9) measured depressive symptoms. Medical history and sociodemographic information were extracted from medical record review. Exploratory factor analyses (EFA) assessed unidimensionality, factor structure, reliability, and criterion and construct validity of the 15-item scale. We used regression models to identify clinical factors associated with sexual dysfunction. Results: EFA suggested retaining 10-items generating a unidimensional scale with strong internal consistency reliability, α = 0.90. Criterion validity assessed using Spearman's coefficient showing that the IBD-MSDS was significantly correlated with all the subscales of the IIEF. The IBD-MSDS was significantly correlated (construct validity) with the PHQ-9 ( P < 0.001) and the composite score for active IBD cases ( P < 0.05). Male sexual dysfunction in IBD was significantly associated with the presence of an ileoanal pouch anastomosis ( P = 0.047), depression ( P < 0.001), and increased disease activity ( P = 0.021). Conclusions: We have developed and validated an IBD-specific scale to assess the psychosexual impact of IBD. This new survey tool may help physicians screen for and identify factors contributing to impaired sexual functioning in their male patients.